2015
DOI: 10.1111/evo.12679
|View full text |Cite
|
Sign up to set email alerts
|

An introgressed wing pattern acts as a mating cue

Abstract: Heliconius butterflies provide good examples of both homoploid hybrid speciation and ecological speciation. In particular, examples of adaptive introgression have been detected among the subspecies of Heliconius timareta, which acquired red color pattern elements from H. melpomene. We tested whether the introgression of red wing pattern elements into H. timareta florencia might also be associated with incipient reproductive isolation (RI) from its close relative, H. timareta subsp. nov., found in the eastern A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 62 publications
5
40
0
Order By: Relevance
“…cydno (Mantel's test: R 2 = 0.64; p = .001) and H. erato – H. e. chestertonii (Mantel's test: R 2 = .51; p = .007) comparisons, but not in H. timareta – H. cydno and H. erato – H. himera comparisons. This is consistent with crosses showing that the former and not the latter pairs experience hybrid sterility and Haldane's rule (McMillan et al., ; Merrill et al., ; Muñoz et al., ; Naisbit et al., ; Salazar et al., ; Sánchez et al., ) and also agrees with the previous observation of reduced shared variation between H. melpomene and both H. timareta and H. cydno on the Z chromosome (Martin et al., ). Note that our simulations suggest that to explain the trend observed in our data, there must be a very strong reduction in migration on the Z chromosome relative to the autosomes (~60% or greater).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…cydno (Mantel's test: R 2 = 0.64; p = .001) and H. erato – H. e. chestertonii (Mantel's test: R 2 = .51; p = .007) comparisons, but not in H. timareta – H. cydno and H. erato – H. himera comparisons. This is consistent with crosses showing that the former and not the latter pairs experience hybrid sterility and Haldane's rule (McMillan et al., ; Merrill et al., ; Muñoz et al., ; Naisbit et al., ; Salazar et al., ; Sánchez et al., ) and also agrees with the previous observation of reduced shared variation between H. melpomene and both H. timareta and H. cydno on the Z chromosome (Martin et al., ). Note that our simulations suggest that to explain the trend observed in our data, there must be a very strong reduction in migration on the Z chromosome relative to the autosomes (~60% or greater).…”
Section: Resultssupporting
confidence: 90%
“…Using the absolute divergence on the autosomes as a proxy for gene flow, we find a pattern of increased Z/A divergence ratios for species pairs with known postzygotic reproductive barriers (Figure 9). Z/A divergence ratios are signifi- Merrill et al, 2012;Muñoz et al, 2010;Naisbit et al, 2002;Salazar et al, 2005;S anchez et al, 2015) and also agrees with the previous observation of reduced shared variation between H. melpomene and both H. timareta and H. cydno on the Z chromosome .…”
Section: Sex-linked Incompatibilities Increase Z/a Absolute Divergesupporting
confidence: 89%
See 1 more Smart Citation
“…While mel is found throughout much of South and Central America, cyd is largely restricted to the west of the Andes and the inter-Andean valleys, where it overlaps with the western populations of mel, whereas tim occurs only on the eastern slopes of the Andes, where it co-occurs with the eastern populations of mel. In addition to strong assortative mating based on chemical cues and wing patterns in the case of cyd and mel [27][28][29][30], and mainly chemical cues between mel and tim [29,31,32], both species pairs show ecological differences as well as partial hybrid sterility [29,30,[33][34][35][36][37] (and see [29] for a review). Nevertheless, previous studies have revealed surprisingly pervasive admixture between these species in sympatry, most likely explained by a low rate of ongoing hybridisation over an extended period of time [1,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been suggested that male pheromones play a role in pre-mating barriers in Heliconius butterflies. Male H. timareta florencia and H. melpomene malleti, closely related co-mimics, court female wing models of both species equally, but interspecific mating is rare (Giraldo et al, 2008;Sánchez et al, 2015;Mérot et al, 2017).…”
Section: Discussionmentioning
confidence: 99%